Contação de histórias na perspectiva de professoras contadoras: possibilidade de atuação. - Vasconcelos, Roger Andrei de Castro (My University, 2018)
This study aims to investigate storytelling as a procedure of mediation for literary reading in order to contribute to the qualification of literary instruction in primary education. It has opted for a qualitative research approach, using the method of bibliographic investigation associated with the technique of interview conducted with five storytellers, teachers of the city of Caxias do Sul municipal education system, in the pursuit of indications of criteria and paths to implement storytelling. The theoretical framework was based in Freire (1998) and Vigotski (2001) regarding education; in Cosson (2009), Candido (2011) and Yunes (2012) to ground literature and literary literacy; and Benjamin (1985), Girardello (2012), Sisto (2012) and Tahan (1945) to reflect on the act of storytelling. This work presented an overview of the educators that perform as storytellers in the city’s municipal education system, their pathways and strategies to motivate reading in school environments. And its results shed light on the reading mediation, the literary literacy and the role of storytellers and their relations with the literary universe. Concluding, the research indicates the necessity of actions such as storytelling to the promotion of literary readers in the society and mainly in the school domain, and also proposes the preparation of educators for reading mediation based on the reality observed in the city of Caxias do Sul.
Este estudo teve por objetivo investigar a contação de histórias como procedimento de mediação de leitura literária, a fim de contribuir para qualificar a educação literária na Educação Básica. Optou-se pela abordagem de pesquisa qualitativa, valendo-se do método de investigação bibliográfica associado à técnica da entrevista com cinco contadoras de histórias, professoras da Rede Municipal de Ensino de Caxias do Sul, em busca do apontamento de critérios e caminhos para implementar a contação de histórias. A fundamentação teórica apoiou-se em Freire (1998) e Vigotski (2001) ao tratar da educação; em Cosson (2009), Candido (2011) e Yunes (2012) sobre literatura e letramento literário e Benjamin (1985), Girardello (2012), Sisto (2012) e Tahan (1945) ao refletir acerca do ato de contar histórias. Apresentou-se, também um panorama dos educadores que atuam como contadores de histórias na Rede Municipal de Caxias do Sul, suas trajetórias e estratégias para o fomento à leitura em ambientes escolares. Os resultados deste estudo discorrem acerca da mediação de leitura, do letramento literário e sobre a função do contador de histórias e suas relações com o universo literário na escola. Como conclusão, este estudo sinaliza a necessidade de ações como a contação de histórias para a promoção de leitores literários na sociedade e, principalmente, no ambiente escolar e ainda propõe a instrumentalização de educadores para mediação de leitura, partindo da realidade presenciada em Caxias do Sul.
Keywords: Contadores de histórias; Letramento; Educação; Story tellers; Literacy; Education